The dramaturgy of Marta Barceló: memory and women’s empowerment - Foguet i Boreu, Francesc; Saumell, Eva (Talía. Revista de estudios teatrales, 2025)
This paper approaches, from a micro-political perspective, the dramaturgy of Marta Barceló (Palma de Mallorca, 1973), one of the most outstanding playwrights of the new Mallorcan stage. First of all, it traces Barceló’s career as an actress and writer, as well as her conception of theatre and the projection of her dramaturgy. This is followed by an analysis of her short plays, Control de passaports (2008), Una casa a Santo Domingo (2011), Germanes de sang (2011), Rates (2012), El cabaret dels somnis vius (2012), Constel·lacions (2016) and Ahmed/Ahme/Ahm/Ah/A (2017), which already hint at some of the themes she will explore in her longer plays, such as individual and collective memory, linked to female identity. Thirdly, the exhibition examines his major works, Maria? (2009), Tocar mare (2019), Anar a Saturn i tornar (2021), Zona inundable (2022) and Contrapropuestas (2023), in which Barceló delves into the intimate experiences of women, their memory and their present, their illnesses and their interpersonal ties. Finally, an in-depth reading of Abans que arribi l’alemany (2018), a play about Alzheimer's disease, is proposed as a paradigm of empowerment and resilience in difficult situations of the anti-heroines who are the protagonists of Barceló's dramaturgy.
Keywords: Catalan dramaturgy; micro-politics; Marta Barceló; intimate memory; empowerment of women